Timing of Angiography and Outcomes in High-Risk Patients With Non–ST-Segment–Elevation Myocardial Infarction Managed Invasively: Insights From the TAO Trial (Treatment of Acute Coronary Syndrome With Otamixaban). Issue 20 (14th November 2017) - Deharo, Pierre; Ducrocq, Gregory; Bode, Christoph; Cohen, Marc; Cuisset, Thomas; Mehta, Shamir R.; Pollack, Charles; Wiviott, Stephen D.; Elbez, Yedid; Sabatine, Marc S.; Steg, Philippe Gabriel
Abstract : Background: In patients with non–ST-segment–elevation myocardial infarction (NSTEMI) and GRACE (Global Registry of Acute Coronary Events) score >140, coronary angiography (CAG) is recommended by European and American guidelines within 24 hours. We sought to study the association of very early (ie, ⩽12 hours), early (12–24 hours), and delayed (>24 hours) CAG in patients with NSTEMI with GRACE score >140 with ischemic outcomes. Methods: The TAO trial (Treatment of Acute Coronary Syndrome With Otamixaban) randomized patients with NSTEMI and CAG scheduled within 72 hours to heparin plus eptifibatide versus otamixaban. In this post hoc analysis, patients with a GRACE score >140 were categorized into 3 groups according to timing of CAG from admission (<12, ≥12–<24, and ≥24 hours). The primary ischemic outcome was the composite of all-cause death and myocardial infarction within 180 days of randomization. Results: CAG was performed in 4071 patients (<12 hours, n=1648 [40.5%]; 12–24 hours, n=1420 [34.9%]; ≥24 hours, n=1003 [24.6%]). With CAG ≥24 hours as a reference, CAG from 12 to 24 hours was not associated with a lower risk of primary ischemic outcome at 180 days (odds ratio, 0.96; 95% confidence interval, 0.75–1.23), whereas CAG <12 hours was associated with a lower risk of death and myocardial infarction (odds ratio, 0.71; 95% confidence interval, 0.55–0.91). Performing CAG <12 hours was also associated with a lower risk of death and myocardial infarction (odds ratio, 0.76; 95% confidence interval, 0.61–0.94; P =0.01) compared with CAG performed at 12 to 24 hours. No difference was observed in bleeding complications. Conclusions: In patients with high-risk NSTEMI, undergoing CAG within the initial 12 hours after admission (as opposed to later, either 12–24 or ≥24 hours) was associated with lower risk of ischemic outcomes at 180 days. Abstract : Supplemental Digital Content is available in the text.